Liberalisation policy: Need for people oriented approach - Rao, V. Bhaskara (1996)
The author examines liberalisation policy with reference to the workers. He points out its inherent deficiencies causing more unemployment, enhancing insecurity in employment, and casualising the labour. Emphasising the need for adopting a people-centred approach to remedy it, he briefly but critically examines the record of performance of governments of Narasimha Rao and the present United Front to point out their failures in this regard. - Reproduced
Keywords: Liberalization - India; Economic liberalization